Latihan Skipping dan Box Jump terhadap Ketepatan Jump Smash Forehand dalam Permainan Bulu Tangkis di MAN 2 Medan - Try Nita Sinaga; Josua Halomoan Aritonang; Trinalia Silalahi; Rinaldi Rahman Hutagalung (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze the impact of skipping and box jump exercises on the accuracy of the forehand jump smash in badminton among students at MAN 2 Medan. The research uses a descriptive qualitative approach, incorporating observation, interviews, and documentation. A total of 20 students participating in the extracurricular badminton program at MAN 2 Medan were selected as subjects. Skipping and box jump exercises were conducted over a period of 8 weeks, with a frequency of 3 times per week. The results of the study showed that skipping and box jump exercises significantly improved leg muscle strength, explosive power, and wrist flexibility, all of which contributed to enhanced forehand jump smash accuracy. Students who had previously struggled with aiming their smashes were now able to execute more precise and powerful shots. Interviews with both coaches and students confirmed that these exercises were not only effective in improving physical abilities but also in boosting the students' confidence during matches. Skipping and box jump exercises can be applied as effective training methods for developing jump smash techniques in badminton.